2010
DOI: 10.1186/scrt28
|View full text |Cite
|
Sign up to set email alerts
|

The pregnancy hormones human chorionic gonadotropin and progesterone induce human embryonic stem cell proliferation and differentiation into neuroectodermal rosettes

Abstract: IntroductionThe physiological signals that direct the division and differentiation of the zygote to form a blastocyst, and subsequent embryonic stem cell division and differentiation during early embryogenesis, are unknown. Although a number of growth factors, including the pregnancy-associated hormone human chorionic gonadotropin (hCG) are secreted by trophoblasts that lie adjacent to the embryoblast in the blastocyst, it is not known whether these growth factors directly signal human embryonic stem cells (hE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 66 publications
2
31
0
Order By: Relevance
“…Although the hCG molecule was the first marker produced by an embryo identified in the spent embryo culture media (3), no further attempts to establish its use as a potential marker of embryo competence has been reported to our knowledge. Its specific function at this stage of embryonic development is currently not known (3,22,23). However, recent studies have suggested that the hCG molecule may be involved in the growth and development of the embryoblast at the early stages and implantation at the later stages of development (23).…”
Section: Discussionmentioning
confidence: 98%
“…Although the hCG molecule was the first marker produced by an embryo identified in the spent embryo culture media (3), no further attempts to establish its use as a potential marker of embryo competence has been reported to our knowledge. Its specific function at this stage of embryonic development is currently not known (3,22,23). However, recent studies have suggested that the hCG molecule may be involved in the growth and development of the embryoblast at the early stages and implantation at the later stages of development (23).…”
Section: Discussionmentioning
confidence: 98%
“…For example, several studies have reported that hormones affect the proliferation and differentiation capacities of human or mouse MSCs (Kuo et al, 2013;Yazawa et al, 2014). Since the levels of sex hormones fluctuate during a woman's life, proliferation and differentiation of ADSCs might also be affected (Gallego et al, 2010;Hirschberg, 2012;Rossi et al, 2014). However, there are no evidence-based studies till date on this subject.…”
Section: Introductionmentioning
confidence: 99%
“…Progesterone, an endogenous and physiologically regulated inhibitor of NF-ÎșB signaling, has been shown to be an important modulator of NF-ÎșB activity following traumatic brain injury, during infection and throughout the menstrual cycle (Brenner et al 2002;Chen et al 2008;Lei et al 2014). Further, progesterone signaling has been found to be essential for embryoid body formation and neurectodermal specification (Gallego et al 2009(Gallego et al , 2010. These crucial progesterone-dependent cell fate decisions also coincide with an increase in BAG2 expression (Barrett et al 2005) suggesting that developmentally regulated NF-ÎșB by progesterone signaling may cause a downstream derepression of NF-ÎșB target genes.…”
Section: Discussionmentioning
confidence: 96%